2023
DOI: 10.37766/inplasy2023.11.0071
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a Scoping Review of Traditional Medicine Research Methods, Methodologies, Frameworks and Strategies

Jennifer Hunter,
Nadine Ijaz,
Suzanne Grant
et al.

Abstract: Support -World Health Organization. Review Stage at time of this submission -Preliminary searches. Conflicts of interest -The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper. Jennifer Hunter has received payments for providing expert advice about traditional, complementary and integrative medicine to industry, government bodies, and non-government organizations. Jennifer Hunter and Suzanne Gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…An abridged version of this protocol was registered on 17 November 2023 on the International Platform of Registered Systematic Review and Meta-analysis Protocols (INPLASY2023110071) ( 58 ). The methodology for this scoping review is informed by JBI guidelines ( 56 ), and will be reported according to the Preferred Reporting Items for Systematic Review and Meta-analysis Scoping Review extension (PRISMA-ScR) ( 59 ).…”
Section: Methodsmentioning
confidence: 99%
“…An abridged version of this protocol was registered on 17 November 2023 on the International Platform of Registered Systematic Review and Meta-analysis Protocols (INPLASY2023110071) ( 58 ). The methodology for this scoping review is informed by JBI guidelines ( 56 ), and will be reported according to the Preferred Reporting Items for Systematic Review and Meta-analysis Scoping Review extension (PRISMA-ScR) ( 59 ).…”
Section: Methodsmentioning
confidence: 99%